The Impact of Technological Pedagogical and Content Knowledge on Teacher Professional Development in Technology Integration Practices - Handini, Oktiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study aims to explore the impact of TPACK on technology integration practices among teachers.This study aims to determine whether TPACK has an impact on teachers' technology integration practices in learning activities. This study is a descriptive qualitative study with a literature study method. The type of research used is library research, namely research that uses library data to be studied more deeply and reviewed in order to obtain objective results. The results of the study indicate that teachers' TPACK has an impact on the development of teacher professionalism related to technology integration in learning. Technology in learning makes learning more innovative and helps teachers experience a more productive teaching process. In conclusion, the TPACK framework can develop teacher professionalism in facing the challenges of 21st century learning to teach with technology. The use of technology in learning will be able to improve the quality of learning so that it has an impact on learning achievement and student involvement in learning.